Aortic valve endocarditis by Actinomyces odontolyticus and Gemella morbillorum oral pathogens. (2021) - Patel, Kishan; MacDonald, Matt; Hmoud, Hosam; Czinn, Eric; Wutawunashe, Caleb; Fisher, Perry
Abstract: A 56-year-old female with a history of poor dental hygiene and aortic insufficiency status post aortic valve replacement in 2015 presented with chest pain and fevers. She was found to have portal vein thrombosis, colitis, and infective endocarditis with aortic valve thickening. Blood cultures were positive for Actinomyces odontolyticus and Gemella morbillorum. Transesophageal echocardiogram was positive for aortic root thickening. Patient was treated with ceftriaxone and apixaban with full recovery.